Screening of chitinase-producing rhizosphere actinomycetes and their genetic diversity (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wahyudi AT, Fitriansyah NG, Amri MF, Priyanto JA, Nawangsih AA. 2021. Screening of chitinase-producing rhizosphere actinomycetes and their genetic diversity. Biodiversitas 22: 4186-4192. Soil microbial community, especially rhizosphere actinomycetes, plays an important role in protecting plants from phytopathogenic fungi by producing various agroactive compounds, including mycolytic enzymes particularly chitinase. The objective of this study was to investigate chitinase activity and analyze the diversity of family 19 chitinase genes of actinomycetes isolated from maize and soybean rhizosphere. Of fivety actinimycetes, Seventeen isolates exhibited chitinolytic activities and formed a hydrolytic zone around the colony with chitinolytic index ranging from 0.49±0.01 to 2.15±0.69, qualitatively tested in 0.3% chitin agar medium. Six selected isolates (ARJ 36, ARJ 81, ARJ 15, ARK 17, ARK 143, ARK 103) showed chitinase activities ranging from 0.157±0.04 to 0.440±0.09 U/mL, based on chitinolytic index. The production of chitinase was confirmed by the presence of family 19 chitinase encoding genes from Streptomyces sp. Some conserved regions and essential amino acid residues were also detected. This study suggests that chitinolytic actinomycetes isolated from maize and soybean rhizosphere can be studied further as biological control candidates for controlling phytopathogenic fungi.
Keywords: chitinase, family 19 chitinase gene, rhizosphere Actinomycetes, Streptomyces sp